Enhancing Laboratory Safety Practices to Minimize Risk - Reham Yosef Johary, Ahmed Abdulrahman Alghamdi, Abdulrahman Mohammed Bamalik, Bashayer Sowillm Alnabati, Fatima Abdullah Almontshrei; Nujud Ali Abu Mohammed, Waleed Ali Alhakami, Nawaf Salim Alharbi, Yasir Ali Alkaabi, Majed Kawayseb Alsulami (Journal of International Crisis and Risk Communication Research, 2024)
A vital component of scientific research, laboratory safety protects both the integrity of experimental findings and the health of researchers. The attitudes and behaviors related to laboratory safety are examined in this essay. Like any other sector, laboratories use similar risk management techniques, such as making a process map to help employees better understand how the process works. After identifying potential mistake sources and evaluating their impact according to severity, chance of occurrence, and detectability, controls and checks are put in place to stop and identify errors before they endanger patients. In order to minimize mishaps and preserve ethical standards in scientific research, the conclusion emphasizes the necessity of ongoing instruction and reinforcement of safety procedures in laboratory settings.